The five temptations of a CEO a leadership fable - Lencioni, Patrick 1965- (Jossey-Bass, 2008)
All managers who fail make the same basic mistakes; they succumb to one, or more, of the five temptations of a manager. In this insightful and entertaining book, Lencioni reveals how to recognise and overcome the major pitfalls of leadership.
Originally published: 1998. - Print version record
Keywords: Leadership -- Fiction; Chief executive officers -- Fiction; Executive ability -- Fiction; Success in business; Leadership; Executive ability; Chief executive officers; Aptitude pour la direction; Succès dans les affaires; Chefs de direction; Leadership; Romans, nouvelles, etc; Chefs de direction; Romans, nouvelles, etc; Aptitude pour la direction; Romans, nouvelles, etc; Fiction